IMPLEMENTASI PENGISIAN SPT PAJAK PENGHASILAN BADAN 2019 ATAS PP 23 TAHUN 2018 PADA PT.K DILAKUKAN OLEH BEN&CO.CONSULTING - Aditya Pradana, (2020)
This Final Assignment report is intended to develop the ability of students to apply the theory learned in the classroom in practice that occurs in the world of work. This Final Report is carried out for 3 months at BEN & Co. Consulting by conducting interviews and direct observation in the relevant tax department to get relevant information related to Corporate Income Tax at BEN & Co. Consulting. The Corporate Income Tax is a state tax which means that every economic addition received by the taxpayer from a business entity comes from preformance and abroad. The purpose of this Final Assignment Report is made to know the Implementation of Filling of the Annual Corporate Income Tax Return on PP 23 of 2018 conducted by BEN & Co. Consulting for PT.K. Based on the results of fieldwork practices, it can be concluded that the implementation of filling the SPT of Corporate Income Tax on PP 23 of 2018 at PT. K was done by BEN & Co. Consulting already carried out in accordance with Law Number 36 of 2008.